The Correlation of Body Composition and Fitness Level of Students in Medical Faculty Unwar - Wayan Rusni; Komang Trisna Sumadewi; Tanjung Subrata (WMJ (Warmadewa Medical Journal), 2019)
Medical students beside they are as a member of the medical rescuer, the team is also to have good physical fitness due to consider that Indonesia involves a disaster drawn area. The study was conducted on a member of Tim Bantuan Medis (Medical Rescuer Team) of FKIK Warmadewa University. This simple random sampling was carried out to choose the sample. The data was analyzed using the Spearman correlation test to find out the correlation between body composition and physical fitness. The result from body composition showed that the highest percentage is in the average category (40.7%) and the smallest percentage is in the fair category (3.35%). Whereas the level of physical fitness that assessed through muscle endurance and cardio-respiratory endurance show a level in the poor as follow 38,5% and 85,7%. The conclusion is a significant correlation (relatively strong)between body composition and physical fitness (muscle endurance and cardio-respiratory endurance ) (r=0.30 dan r=0.18)